An Analysis of the Impact of Age, Work Experience, and Gender on Job Search Duration Among Graduates - Khayru, Rafadi Khan; Darmawan, Didit; Kurniawan, Yulius (Journal of Social Science Studies, 2022)
The imbalance between the size of the labor force and the size of employment opportunities raises the problem of unemployment of educated workers. The problem of unemployment can impact the economic growth of the community. The problem of employment, especially the duration of job search for educated workers, is an important phenomenon that will be explored in this research. This research aims to determine and analyze the influence of age, work experience and gender variables on the length of time looking for work. The type of research conducted in this research is quantitative descriptive research. The data used in this research are primary data obtained from a questionnaire with a sample size of 50 working graduates. The data will be analyzed using multiple regression analysis methods using SPSS software. From the results of data analysis that has been done, the following conclusions can be obtained: 1) the age variable has a positive and significant effect on job search duration; 2) the work experience variable has a positive and significant effect on job search duration; 3) the gender variable has a positive and significant effect on job search duration; and 4) the three independent variables (age, work experience, and gender) simultaneously also have a significant effect on job search duration.